The Disharmony In The Appointment Of Indonesian National Armed Forces (TNI) Personnel To Civilian Positions - Juan Fattah Fachrezy; Muh. Ali Masnun; Ramadhani Salman Alfarizi (NOVUM : JURNAL HUKUM, 2026)
This research is motivated by the enactment of Law Number 3 of 2025 concerning Amendments to Law Number 34 of 2004 on the Indonesian National Armed Forces (TNI), which has generated controversy regarding the expansion of civilian positions that may be occupied by active TNI personnel. The provision is considered to have the potential to weaken the principle of civilian supremacy, create political conflicts of interest, and cause disharmony with Law Number 28 of 1999 concerning State Administrators Who Are Clean and Free from Corruption, Collusion, and Nepotism. This study aims to analyze the conformity of dual civilian positions held by TNI personnel with the principle of civilian supremacy and to examine the forms of disharmony between the two laws. This study employs normative legal research using both statutory and conceptual approaches. Legal materials were collected through library research consisting of primary, secondary, and tertiary legal sources. The legal materials were analyzed using a prescriptive method in order to provide legal arguments and solutions to the issues examined. The results of the study indicate that the provisions concerning dual civilian positions held by active TNI personnel are not fully consistent with the principle of civilian supremacy because they may lead to military intervention in civilian affairs, political conflicts of interest, human rights violations, and tendencies toward authoritarianism. Furthermore, the revised TNI Law is considered disharmonious with the principles of legal certainty, orderly state administration, public interest, professionalism, and accountability as stipulated in Law Number 28 of 1999. Therefore, clearer legal norms and stricter limitations on the involvement of active TNI personnel in civilian positions are necessary to safeguard democratic principles, civilian supremacy, and legal certainty in Indonesia.